Prenatal Testing for Selection against Disabilities - Mahowald, Mary B. (Cambridge quarterly of healthcare ethics, 2007)
Disability rights advocates sometimes claim that prenatal tests to select against disabilities discriminate against people with disabilities. The “expressivist argument” that supports this position has been challenged on grounds of the difference between fetuses and born persons. In this essay, I explain why the expressivist argument is valid despite the questionableness of its conclusion, and why the distinction between fetuses and born persons fails to provide an adequate counterargument to the expressivist conclusion. I also consider a compelling argument for prenatal testing to select against disabilities and propose a reformulation of this argument that, I think, supports prenatal testing for disabilities while avoiding discrimination against people born with disabilities.